Salinity Effects on Anionic AEC Surfactant with Crude Oil: IFT, Phase Behavior, Solubilization, Microemulsion Viscosity - Swadesi, Boni; Azmia, Fadhlan Barrul; Pratiknyo, Avianto Kabul; Kurniawan, Aditya; Suwardi (Penerbitan Universitas Trisakti, 2025)
The investigates the influence of NaCl salinity (0–32,000 ppm) on the performance of Alkyl Ethoxy Carboxylate (AEC) anionic surfactants for Enhanced Oil Recovery (EOR), using light crude oil as a model. Salinity fundamentally affects the system's Interfacial Tension (IFT), phase behavior, solubilization, and microemulsion rheology. The objectives were to map these effects and determine the optimal operational salinity and surfactant working concentration. The working concentration of 1.75% w/w was established above the Critical Micelle Concentration (CMC), determined from the breakpoint of the IFT curve versus log AEC concentration. IFT was precisely measured using a spinning-drop tensiometer. Phase behavior was characterized via a salinity scan to map the Winsor I–III–II transition, and the solubilization ratio was calculated from the equilibrium volume of the middle phase. Microemulsion viscosity was measured using a Brookfield DV3T viscometer with a stepwise shear protocol. The key results showed that an optimum salinity window produced ultra-low IFT, led to the formation of Winsor III microemulsions with a balanced oil/water solubilization ratio, and caused a viscosity peak that coincided with the Hydrophilic-Lipophilic Difference (HLD) ≈ 0 conditions. The microemulsions exhibited characteristic shear-thinning behavior across the tested shear rates. Salinity systematically controls the key physicochemical properties of the AEC–crude oil system. The findings provide: selecting the working concentration based on the CMC test and choosing the salinity at HLD ≈ 0 maximize residual oil mobilization while minimizing phase instability risks. Operational implications include precise brine selection, surfactant dosage control, and adaptive staged slug injection strategies.